Investigation of Cement Slurry with Alkali Treated Sisal Fibers for Lost Circulation - Cheng, Xiaowei; Jiao, Shaoqing; Zhang, Hua; Li, Zaoyuan; Guo, Xiaoyang (Asian Journal of Chemistry, 2012)
With the aim to challenge low plugging efficiency of plugging cement slurry caused by poor-dispersed plugging fibers in the cement slurry, the authors used alkali treated sisal fibers as plugging material of cement slurry and studied the plugging efficiency added a different dosage of alkali treated sisal fibers through the modified experimental set-up for lost circulation test. The microstructure, the types and quantities of polar groups in the surface of alkali treated sisal fibers were respectively evaluated by SEM and XPS. The results showed that the cement slurry added 0.3 % sodium hydroxide treated sisal fibers is well proportioned disperse and succeed in blockling less than 4 mm the size of pore or 4 mm the size of fracture. Mean while, the paper noted that the polar groups in the surface of sisal fiber are favourable for sisal fiber bridging and forming blocking zone in a simulated fracture or hole rapidly.